VEGF-VEGFR pathway seems to be the best target in hepatic epithelioid hemangioendothelioma: A case series with review of the literature - YUMUK, PERRAN FULDEN; ÖNEŞ, TUNÇ (MOSBY-ELSEVIER, 2020)
Epithelioid hemangioendothelioma (EHE) is a rare vascular tumor originating from endothelial cells. Clinical aspect of the disease covers a wide spectrum from a low-grade tumor to a fatal cancer. Most common sites of EHE are reported as lung, liver and bone. Hepatic EHE (HEHE) is a clinical form with an incidence of less than 1 person in a million. Due to rarity of the disease, there is no standard therapy established. Surgery and liver transplantation still seem to be the best approach if possible. However, most of the patients present with unresectable or metastatic disease. Many conventional chemotherapeutic agents and antiangiogenic drugs have been reported previously in the literature with inconsistent outcomes. Here we report 4 cases of HEHE, who benefit distinctly from anti-VEGF treatments in different settings. While combination of paclitaxel and bevacizumab resulted in partial response in 3 patients, one of them also achieved long-term disease stabilization with bevacizumab maintenance with no adverse event. Two of the patients had clear benefit from pazopanib during the course of disease. One patient was treated with thalidomide for 18 months with stable disease, and is still being followed without any treatment. Although targeting VEGF-VEGFR pathway seems to be the best approach in HEHE, randomized studies are urgently needed to support these findings. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Epithelioid hemangioendothelioma; hepatic; VEGF; bevacizumab; LIVER; BEVACIZUMAB; THALIDOMIDE